James Gillray : a revolution in satire - Clayton, Tim (The Paul Mellon Centre for Studies in British Art, 2022)
Described by one contemporary as the "Prince of Caricatura," James Gillray (1757-1815) was the late eighteenth and early nineteenth century's most famous and prolific graphic satirist. This definitive biographical study explores Gillray's work through his friends, collaborations, and connections, and places it in the context of the world of print and political satire at a time when revolution and war erupted around the globe. As well as an obsessive artist, Gillray was a hard-working art-businessman who struggled to make a living in politically exciting but difficult financial circumstances. Exploring Gillray's life -his relations with his publishers, his patrons, other artists, and politicians, and the pressures that made him publish -sheds new light on contemporary anxieties about artistic independence, the role of propaganda, and the increasing political importance of public opinion.0Lavishly illustrated, James Gillray also explores the artist's early involvement in the production of previously unknown erotic prints, nearly all of which were deliberately destroyed by moral crusaders during the 1790s